Corporate Life Cycle and the Explanatory Power of Risk Measures versus Performance Measures - Hamed Omrani; Saber Samadi .; Ahmad Kazemi Margavi .; Hamid Asadzadeh .; Hemad Nazari . (Journal of Education and Vocational Research, 2011)
The major aim of this paper is to compare the explanatory power of risk measures versus performance measures in different life-cycle stages. To test the hypotheses, first, sample firms were classified into three life-cycle stages (Growth, Mature and Decline). Then, using regression models and Vuong's Z-statistic, the hypotheses were investigated. In this study, financial information of 75 firms which were accepted at Tehran’s Stock Exchange (TSE) from 2003 to 2008 (450 firm-years) was examined. The results of this study show that in growth and decline stages, the explanatory power of risk measures is significantly higher than performance measures and in mature stage, the opposite is true.